Runtuhnya kerajaan Hindu-Jawa dan timbulnya negara-negara Islam di Nusantara - Muljana, Slamet, Prof. Dr., 1922-; Adam, Asvi Warman, 1954- (Yogyakarta : LKiS Yogyakarta, 2005)
History of the fall of Hindu kingdoms in Java and the rise of Islamic sultanates in Indonesia from the 14th to 16th century
Keywords: Hinduism -- Indonesia -- Java; Islam -- Indonesia; Indonesia -- Civilization -- Indic influences